Common Iliac Artery and Vein Injury Associated with Pelvic Fracture - Jha, Daman Kumar; Lakhey, Shishir; Rana, Raj; Rajbanshi, BG; Acharya, A; Rai, P; Chitrakar, Niva; Thakur, J (Nepal Orthopaedic Association Journal, 2021)
This study reports a case of pelvic fracture associated with left common iliac artery and vein injury that was managed with vascular repair and fracture fixation. A 65 years old female presented to another center with fractures of the left iliac wing, anterior wall of left acetabulum, both alae of S1 vertebra and hypovolemic shock after a road traffic accident. She was initially admitted to the center and later transferred to our center 5 days post injury after hemodynamic stabilization. On admission,there was no obvious neurovascular deficit and the vitals were stable. Pre-op consultation was taken from the Vascular surgeons. A definite vessel injury could not be confirmed preoperatively. During surgery for the fracture fixation on 8th day of injury, there was bleeding from left common iliac artery and vein. Vascular repair was done and the fracture was stabilized. Postoperatively, the patient made slow but uneventful recovery and she was discharged .